PERLINDUNGAN HUKUM HAK ASASI MANUSIA INTERNASIONAL TERHADAP IMIGRAN SURIAH - Jastisia, Mentari; Ariska, Dudung Indra (Yustitia, 2021)
Immigrants are people who have fled from their country to other countries where they can be referred to as refugees or asylum seekers. There are legal instruments that regulate and provide protection for them. Arrangements for asylum seekers are contained in the 1967 Declaration of Territorial Asylum, State practice, humanitarian issues, Declaration of Human Rights (UDHR). Meanwhile, the arrangements for refugees are contained in the Convention Relating to the Status of Refugees 1951, Protocol relating to the status of Refugees 1967, International Covenant on Civil and Political Rights (ICCPR). This papers uses a normative juridical method. This juridical approach is because this research analyzes existing legal aspects, and is normative because this research focuses more on the analysis of existing laws and regulations and other regulations, using secondary data, namely scientific references or other scientific writings as study material that can support the completeness of this scientific papers. Regarding legal protection for Syrian immigrants, the same applies to immigrants from other state as regulated in the arrangements that have been regulated. Countries in the European Union implement international human rights law protections for Syrian immigrants residing in European Union countries consistently as mandated in the European Convention on Human Rights, Convention applying the Schengen Agreement dated June 14, 1985, Lisbon treaty, Dublin II Regulation (Council Regulation (EC) 343/2003) 2003. The indication is that there are several countries in the European Union such as Greece, Hungary which refuse and do not want to take more responsibility for their obligations as a State related to the provisions of international human rights law to provide protection for Syrian immigrants. in Europe